Diagnostic Performance of Ultrasonography Compared with Magnetic Resonance Cholangiopancreatography in Patients with Obstructive Jaundice - Tayal, Ashok; Chaudhary, Arbind Kumar (Journal of Bharatpur Hospital, 2026)
BackgroundObstructive jaundice is a common clinical condition requiring accurate imaging for etiological diagnosis. Ultrasonography (USG) is widely used as an initial modality, while magnetic resonance cholangiopancreatography (MRCP) provides detailed biliary imaging. This study aimed to compare the diagnostic performance of USG and MRCP in patients with obstructive jaundice.MethodsThis hospital-based descriptive cross-sectional study was conducted among 86 patients with clinically suspected obstructive jaundice at Kathmandu Medical College, Kathmandu Nepal. All patients underwent both ultrasonography (USG) and magnetic resonance cholangiopancreatography (MRCP), and findings were compared with the final diagnosis, which served as the reference standard. Diagnostic performance was assessed using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, and Cohen’s kappa (κ) for agreement analysis. Data were analyzed using SPSS version 20.ResultsThe most common final diagnosis was choledocholithiasis (41.9%), followed by common bile duct stricture (16.3%) and carcinoma of the head of pancreas (11.6%). MRCP showed higher diagnostic performance than USG across all etiologies. For choledocholithiasis, sensitivity, specificity, and accuracy of MRCP were 96.6%, 92.6%, and 96%, respectively, compared to 78%, 88%, and 84% for USG. For malignant strictures, MRCP achieved 100% sensitivity and 98.8% specificity, while USG showed lower values (82% and 90%). Overall, MRCP demonstrated almost perfect agreement with the final diagnosis (κ = 0.94), whereas USG showed substantial agreement (κ = 0.69).ConclusionMRCP is a more accurate and reliable imaging modality than USG for evaluating the etiology of obstructive jaundice. It demonstrates superior diagnostic performance and higher agreement with the final diagnosis, supporting its use as a preferred diagnostic tool, especially in complex cases.